PENGARUH GENDER TERHADAP KEPUTUSAN PEMBELIAN PRODUK ONLINE (STUDI KASUS TERHADAP MASYARAKAT PONTIANAK) - Diana Fitriani (Universitas Raharja, 2019)
The aim of this research is to figure out the effect of gender to the online shopping product decision on Pontianak society. Two or more ways analysis of variance know as ANOVA 2, the technique analysis used which manual simultaneously interaction factor, interview, observation and questionnaire are the technique of data collection implemented. Non probability sampling technique with purposive random sampling method with 100 respondents. The result show that there are 50% both the female and male respondents, 45% respondents age range 23-27, 35% last education as bachelor, 38% as private staff and 54% monthly income range 3.000.000., - 4.999.000. The result above indicate hat in this research the adult buyers characteristics, work with fixed income have tendency in shopping products offered online since of the feminine feeling and more sensitive when looking at online media